Rubbish and recycling - Turnbull, Stephanie; Fox, Christyan; Lawrence, Michelle; Slane, Andrea (London usborne house, 2019)
Why do we need to recycle and what happens to our rubbish after it is taken away? Children can learn about the finite nature of natural resources, what rubbish is not recyclable and the impact it has on our planet, and how recycling is sorted, processed and turned into new products. This is a straightforward introduction to a vital subject
Science (environment)
Keywords: Environment